Analyse et structure du travail de Jean-Marie Faverge - Régis Ouvrier-Bonnaz (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article by Régis Ouvrier-Bonnaz is the first in a series that will appear in this history section. It presents PISTES’ readers with an article by Jean-Marie Faverge, published in 1952. According to the author, this article is important due to its questioning of the analytical methods used at that time to study human behaviour in the workplace. Also, it announces the start of the francophone ergonomics movement based on activity analysis.